2023
DOI: 10.1007/s00068-022-02191-8
|View full text |Cite
|
Sign up to set email alerts
|

Techniques for mesoappendix transection and appendix resection: insights from the ESTES SnapAppy study

Abstract: Introduction Surgically managed appendicitis exhibits great heterogeneity in techniques for mesoappendix transection and appendix amputation from its base. It is unclear whether a particular surgical technique provides outcome benefit or reduces complications. Material and methods We undertook a pre-specified subgroup analysis of all patients who underwent laparoscopic appendectomy at index admission during SnapAppy (ClinicalTrials.gov Registration: NCT043… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
2

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 38 publications
(44 reference statements)
0
2
0
Order By: Relevance
“…Some studies have found that laparoscopic surgery minimally impacts human immune function and injury, making postoperative incision infections less likely [113,114]. Therefore, the choice of surgical method is particularly crucial, with a preference for laparoscopic surgery when possible [115,116]. Research indicates that in a single-center randomized controlled trial, the postoperative incision infection rate for patients undergoing laparoscopic surgery for colorectal cancer was 4.9% (47/961), signi cantly lower than the open surgery group (9.6%, 95/986) [117,118,119,120].…”
Section: Surgical Methods Include Traditional Open Surgery and Laparo...mentioning
confidence: 99%
“…Some studies have found that laparoscopic surgery minimally impacts human immune function and injury, making postoperative incision infections less likely [113,114]. Therefore, the choice of surgical method is particularly crucial, with a preference for laparoscopic surgery when possible [115,116]. Research indicates that in a single-center randomized controlled trial, the postoperative incision infection rate for patients undergoing laparoscopic surgery for colorectal cancer was 4.9% (47/961), signi cantly lower than the open surgery group (9.6%, 95/986) [117,118,119,120].…”
Section: Surgical Methods Include Traditional Open Surgery and Laparo...mentioning
confidence: 99%
“…They also catalog their experience in applying this approach to achieve two specific goals: (1) identifying knowledge gaps regarding the optimal treatment for appendicitis as a hypothesis-generating launchpad for future interventional RCTs, and (2) describing the gap between evidence-based practice guidelines [6] and "real world" selective application as a lens through which to assess the variability in surgical outcomes. Tackling some of the controversies in current care of the patient with acute appendicitis, the ESTES SnapAppy collaborative explores technical aspects of surgical management (including the use of staplers and energy devices at key portions of the operation), operating surgeon experience, mentorship and graded trainee autonomy, and contemporary surgical outcomes following appendectomy across Europe, North America and the Middle East, particularly in the context of an evolving COVID pandemic [7][8][9][10].…”
mentioning
confidence: 99%